Volume 1: 21st Biennial Conference on Mechanical Vibration and Noise, Parts A, B, and C 2007
DOI: 10.1115/detc2007-35197
|View full text |Cite
|
Sign up to set email alerts
|

Pareto Optimal Structural Models and Predictions Consistent With Data and Modal Residuals

Abstract: A multi-objective identification method for model updating based on modal residuals is proposed. The method results in multiple Pareto optimal structural models that are consistent with the measured modal data, the class of models used to represent the structure and the modal residuals used to judge the closeness between the measured and model predicted modal data. The conventional single-objective weighted modal residuals method for model updating is also used to obtain Pareto optimal structural models by var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A heuristic sequential sensor placement algorithm is then used to predict the optimal sensor configuration. Work by Ntotsios et al [15], and earlier works by Udwadia [16] and Heredia-Zavoni et al [17], showed the importance of addressing the issue of uncertainty in handling the optimal sensor configuration. Other researchers [18,19] also reported the use of information entropy and information functions such as Fisher information to formulate the objective function for optimal sensor allocations.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A heuristic sequential sensor placement algorithm is then used to predict the optimal sensor configuration. Work by Ntotsios et al [15], and earlier works by Udwadia [16] and Heredia-Zavoni et al [17], showed the importance of addressing the issue of uncertainty in handling the optimal sensor configuration. Other researchers [18,19] also reported the use of information entropy and information functions such as Fisher information to formulate the objective function for optimal sensor allocations.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, Li et al [14] obtained a vector of sensor placement indices based on the weighted components of the mode shape matrix corresponding to the sensor position. Ntotsios et al [15] presented another approach that addresses the stochastic nature of the sensor measurements. The sensor allocation problem is handled within the context of uncertainty and information entropy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation